Relationship Between Frequency Domain Indicators of Heart Rate Variability and Both Age and Duration of Illness in Patients with Headache: A Cross-Sectional Study - Jong-Ho Kim; Jong-Hee Sohn; Sung-Mi Hwang; Jae-Jun Lee; Young-Suk Kwon (Biomedicines)
Background/Objectives: One of the most prevalent neurological conditions in the world, headaches impact a large number of people. Patients who experience headaches often have autonomic nervous system dysfunction, which can influence the onset and duration of headaches. Heart rate variability (HRV) serves as an indicator of the autonomic nervous system’s activity and balance. In this study, we looked at the frequency domain of HRV in relation to age and headache duration in patients who had headaches. Methods: This cross-sectional research is a secondary analysis that makes use of data gathered from previously registered study projects. They were adult males and females aged 19 to 80. HRV was recorded in three channels over the course of 20 min using a 256 Hz sampling interval. HRV frequency domain was utilized to analyze the relationship between HRV and headache duration as well as between HRV and age. Results: In a smooth curve through the scatterplot using the locally estimated scatterplot smoothing line, low frequency/high frequency (LF/HF) declined beyond around 60 years of age, while the total power (TP) decreased until about 50 years of age, after which there was no discernible change. The duration of the headache did not significantly correlate with LF/HF or TP. However, TP decreased with age in the multivariate linear regression model (coefficient [95% confidence interval]: −0.003 [−0.003–−0.002]). Conclusions: There may be associations between HRV indices and age, but these associations may not be linear.